Associations between Extracellular Matrix Protein 1 Gene Polymorphism and Progression of Liver Disease. (14th October 2022) - He, Xiuting; Liu, Ting; Zhang, Rui; Li, Xu
Abstract : Background . Our study aimed to investigate the relationship between extracellular matrix 1 ( ECM1) gene polymorphism and progression of liver fibrosis in the Chinese population. Methods . A total 656 patients with hepatitis B virus (HBV) infection and 298 healthy individuals of the Chinese Han population were recruited for a retrospective case-control study. Of the disease group, 104 cases had chronic hepatitis B (CHB), 266 had LC, and 286 had hepatocellular carcinoma (HCC). Subjects were frequency-matched according to age and gender. Polymorphisms of the ECM1 gene were examined using the MassARRAY SNP genotyping method. Results . There were no associations between genotype and allele frequencies of ECM1 rs3737240 and rs13294 loci with the risk of CHB and CHB-related HCC. After adjustment for age, sex, smoking status, and drinking habits, the GT genotype was dramatically related to a reduced risk of chronic HBV infection in both non-HCC (OR = 0.68, 95% CI: 0.49-0.94) and total chronic HBV infection patients (OR = 0.75, 95% CI: 0.56-1.00). Haplotype analyses revealed twelve protective haplotypes against total chronic HBV infection and four against non-HCC chronic HBV infection. Conclusion . ECM1 gene polymorphism in rs3834087 and rs3754217 loci is associated with a reduced risk of chronic HBV infection but not with liver fibrosis development and the occurrence of HCC.